2009
DOI: 10.1097/scs.0b013e318199219b
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Stromal Eosinophilic Infiltration in Oral Squamous Cell Carcinoma

Abstract: Tumor-associated tissue eosinophilia (TATE) has been described in many sites, including head and neck. The aim of this study was to investigate the prevalence and possible role of TATE as a prognostic factor in oral squamous cell carcinoma (OSCC). Seventy-six consecutive patients with a diagnosis of OSCC were evaluated, and the number of eosinophils was obtained in 3 different areas in the tumor. The possible role of TATE as a prognostic factor in OSCC was investigated with respect to tumor differentiation; pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
3
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 24 publications
2
51
3
3
Order By: Relevance
“…Oliviera et al [8] reported equivalent 5-year and 10-year overall survival and disease-free survival rates for both OSCC with intense and absent/mild tissue eosinophilia. Likewise, Tadbir et al [24] concluded that TATE has no correlation with prognostic parameter in OSCC. Leighton et al [6] assessed the presence of TATE in nasopharyngeal carcinoma and found that TATE was not significantly associated with local recurrence, distant metastasis, and survival.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Oliviera et al [8] reported equivalent 5-year and 10-year overall survival and disease-free survival rates for both OSCC with intense and absent/mild tissue eosinophilia. Likewise, Tadbir et al [24] concluded that TATE has no correlation with prognostic parameter in OSCC. Leighton et al [6] assessed the presence of TATE in nasopharyngeal carcinoma and found that TATE was not significantly associated with local recurrence, distant metastasis, and survival.…”
Section: Discussionmentioning
confidence: 99%
“…Alkhabuli and High [31] did not find any correlation between eosinophil density and SCC differentiation in cases of SCC of tongue. Similarly, Tadbir et al [24] failed to report any significant correlation between TATE and tumor differentiation in patients of OSCC. Also, Rahrotaban et al [25] demonstrated no significant correlation between TATE and histopathologic grading, but it was lower in poorly differentiated group than in others in cases of HNSCC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tumour-associated tissue eosinophilia (TATE) has been reported in diverse sites [14, 35, 4753] including the head and neck region [6, 7, 5465] (Figure 2). …”
Section: Prognostic Value Of Eosinophils In Oral Squamous Cell Carmentioning
confidence: 99%
“…Recently, eosinophilia has been investigated in head and neck carcinomas, especially the oral cavity carcinomas [7][8][9][10][11]. Although it has been shown that the relationship between eosinophil count and prognosis is statistically significant, it still remains controversial [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%